2003
DOI: 10.1128/jvi.77.2.905-914.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Human Cytomegalovirus UL97 Protein Kinase, an Antiviral Drug Target, Is Required at the Stage of Nuclear Egress

Abstract: Human cytomegalovirus encodes an unusual protein kinase, UL97, that activates the established antiviral drug ganciclovir and is specifically inhibited by a new antiviral drug, maribavir. We used maribavir and a UL97 null mutant, which is severely deficient in viral replication, to determine what stage of virus infection critically requires UL97. Compared with wild-type virus, there was little or no decrease in immediate-early gene expression, viral DNA synthesis, late gene expression, or packaging of viral DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

23
238
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(261 citation statements)
references
References 40 publications
(35 reference statements)
23
238
0
Order By: Relevance
“…HCMV mutants lacking UL97 produce approximately 10 to 1,000 fold fewer infectious particles than wild-type virus during replication in cultured cells (7,(15)(16)(17)(18). Specific defects of these mutants during viral replication include reduced viral DNA synthesis, impaired exit of capsids from the nucleus (nuclear egress), and altered intracellular localization of virion components; pharmacological inhibition of UL97 results in similar phenotypes (8,10,15,17,19,20).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…HCMV mutants lacking UL97 produce approximately 10 to 1,000 fold fewer infectious particles than wild-type virus during replication in cultured cells (7,(15)(16)(17)(18). Specific defects of these mutants during viral replication include reduced viral DNA synthesis, impaired exit of capsids from the nucleus (nuclear egress), and altered intracellular localization of virion components; pharmacological inhibition of UL97 results in similar phenotypes (8,10,15,17,19,20).…”
mentioning
confidence: 89%
“…Specific defects of these mutants during viral replication include reduced viral DNA synthesis, impaired exit of capsids from the nucleus (nuclear egress), and altered intracellular localization of virion components; pharmacological inhibition of UL97 results in similar phenotypes (8,10,15,17,19,20). Our discovery that UL97 directly phosphorylates pRb prompted us to examine the roles that both UL97 and pRb play during HCMV infection.…”
mentioning
confidence: 99%
“…Structural analysis of purified virions of several herpesviruses, including HSV, CMV, and EBV, indicate that these protein kinases are asso-ciated with virus particles (2,12,37,50,52); thus, the kinases are in a position to influence virion assembly and events that take place after entry of the virion into the cell. A number of studies using kinase-null viral mutants demonstrated the importance of the kinase for regulating viral gene expression, replication, tissue tropism, or infection in animal models (7,11,26,35,41,48). Various studies have implicated the viral protein kinase in influencing viral gene expression (6,58), viral DNA replication (27,52,53), or nucleocapsid egress from the nucleus during virus assembly (26,34,53).…”
mentioning
confidence: 99%
“…Various studies have implicated the viral protein kinase in influencing viral gene expression (6,58), viral DNA replication (27,52,53), or nucleocapsid egress from the nucleus during virus assembly (26,34,53). The importance of the viral protein kinase (vPK) for HSV and CMV replication is supported by studies showing that changes in this gene can confer resistance to certain antiviral agents (e.g., ganciclovir) (7,26). Taken together, these studies demonstrate that the conserved herpesvirus protein kinases impact multiple steps in viral replication.…”
mentioning
confidence: 99%
See 1 more Smart Citation